Strategi Pemanfaatan Generative Artificial Intelligence dalam Manajemen Media Dakwah Digital: Peluang, Efisiensi, dan Tantangan Etika Komunikasi Islam - Ahmad Zein Daulay; Susi Purnamasari Gulo; Sholeh Fikri (PT Anugerah Literasi Indomedia, 2026)
The development of Generative Artificial Intelligence (GenAI) has brought significant transformations to the management of digital da'wah media, requiring the adaptation of Islamic communication strategies in the technological era. This technology offers various opportunities to support the production, distribution, and management of da'wah content more effectively while expanding audience reach through diverse digital platforms. This study employed a qualitative approach using a library research method. Data were collected from relevant journal articles, books, and academic documents and analyzed through content analysis to identify themes, patterns, and conceptual relationships regarding the utilization of GenAI in digital da'wah media management. The findings indicate that GenAI has substantial potential to enhance the effectiveness of da'wah through content personalization, broader audience engagement, and the development of technology-based religious services. Furthermore, GenAI improves the efficiency of da'wah media management through content production automation, audience analysis, and the optimization of religious information distribution. However, its implementation also presents several challenges, including the validity of religious information, algorithmic bias, the potential shift of religious authority, and the risk of diminishing the humanistic dimension of da'wah communication. Therefore, the application of GenAI in digital da'wah media requires proper management that incorporates the principles of Islamic communication ethics to ensure that technological utilization remains aligned with the objectives and values of Islam. Perkembangan Generative Artificial Intelligence (GenAI) telah menghadirkan transformasi signifikan dalam pengelolaan media dakwah digital yang menuntut adaptasi strategi komunikasi Islam di era teknologi. Teknologi ini menawarkan berbagai peluang dalam mendukung proses produksi, distribusi, dan pengelolaan konten dakwah secara lebih efektif serta mampu menjangkau audiens yang lebih luas melalui berbagai platform digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Data diperoleh dari artikel jurnal, buku, dan dokumen akademik yang relevan, kemudian dianalisis menggunakan teknik content analysis untuk mengidentifikasi tema, pola, dan keterkaitan konsep terkait pemanfaatan GenAI dalam manajemen media dakwah digital. Hasil kajian menunjukkan bahwa GenAI berpotensi meningkatkan efektivitas dakwah melalui personalisasi konten, perluasan jangkauan audiens, serta pengembangan layanan keagamaan berbasis teknologi. Selain itu, GenAI mampu meningkatkan efisiensi pengelolaan media dakwah melalui otomatisasi produksi konten, analisis audiens, dan optimalisasi distribusi informasi keagamaan. Namun, pemanfaatannya juga menghadirkan tantangan berupa validitas informasi keagamaan, bias algoritma, potensi pergeseran otoritas keagamaan, serta risiko berkurangnya dimensi humanistik dalam komunikasi dakwah. Oleh karena itu, penerapan GenAI dalam media dakwah digital memerlukan pengelolaan yang memperhatikan prinsip-prinsip etika komunikasi Islam agar pemanfaatan teknologi tetap sejalan dengan tujuan dan nilai-nilai dakwah Islam.